Molecular cloning and analysis of Suncus murinus group IIA secretary phospholipase A2 expression. (November 2019) - Takemi, Shota; Nishio, Ryo; Taguchi, Hayato; Ojima, Shiomi; Matsumoto, Mio; Sakai, Takafumi; Sakata, Ichiro
Abstract: The intestinal epithelial monolayer forms a mucosal barrier between the gut microbes and the host tissue. The mucosal barrier is composed of mucins and antimicrobial peptides and proteins (AMPs). Several animal studies have reported that Paneth cells, which occupy the base of intestinal crypts, play an important role in the intestinal innate immunity by producing AMPs, such as lysozyme, Reg3 lectins, α-defensins, and group IIA secretory phospholipase A2 (GIIA sPLA2). The house musk shrew ( Suncus murinus ) has only a few intestinal commensal bacteria and is reported to lack Paneth cells in the intestine. Although the expression of lysozyme was reported in the suncus intestine, the expression of other AMPs has not yet been reported. Therefore, the current study was focused on GIIA sPLA2 expression in Suncus murinus . GIIA sPLA2 mRNA was found to be most abundant in the spleen and also highly expressed in the intestine. Cells expressing GIIA sPLA2 mRNA were distributed not only in the crypt, but also in the villi. In addition, intragastric injection of lipopolysaccharide increased GIIA sPLA2 expression in the small intestine of suncus. These results suggest that suncus may host unique AMP-secreting cells in the intestine. Highlights: GIIA sPLA2 was identified in the Suncus murinus that has only a few intestinal commensal bacteria. GIIA sPLA2 mRNA expression was found in various tissues, with enriched expression particularly in the spleen and intestine. GIIA sPLA2 mRNA-expressing cells were distributed in the crypt and the villi of S. murinus intestine. Intragastric injection of LPS increased GIIA sPLA2 mRNA expression throughout the small intestine of S. murinus .